Dust exposure, pneumoconiosis, and mortality of coalminers. Issue 11 (November 1985) - Miller, B G; Jacobsen, M
Abstract : General mortality in approximately 25 000 British coalminers over 22 year periods ending in 1980 was 13% lower on average than in English and Welsh men in the same regions of Britain. There were significant within region variations between collieries, and standardised mortality ratios increased during the later years of the follow up, approaching or slightly exceeding 100 in most of the 20 coalmines studied. Age specific comparisons of 22 year survival rates were made in subgroups. Relative risks of death from all non-violent causes for men with the earliest stage of progressive massive fibrosis (PMF category A), compared with risks in miners with no pneumoconiosis (category O), ranged from 1.2 in those aged 55-64 initially to 3.5 for those aged 25-34. Mortality in miners with higher categories of PMF (B or C) was even more severe. Survival rates in men with category 1 simple pneumoconiosis were about 2% to 3% lower than in miners with radiographs classified as category O, but there was no consistent evidence of an increase in mortality with increasing category of simple pneumoconiosis. Mortality from all non-violent causes increased systematically with increases in estimates of exposure to dust before the start of the follow up. That gradient was attributable primarily to deaths certified as due to pneumoconiosis and those recorded as due to bronchitis and emphysema (p less than 0.001). There was some evidence of a dust related increase in deaths from cancers of the digestive system (p approximately equal to 0.05), but none of an association between exposure to coalmine dust and lung cancer. Lung cancer mortality, assessed over 17 year periods, was about 5.5 times higher in smokers than in life long non-smokers. Smokers with no pneumoconiosis had slightly higher lung cancer death rates than smokers with pneumoconiosis. We conclude that miners exposed to excessive amounts of respirable coalmine dust are at increased risk of premature death, either from progressive massive fibrosis or from chronic bronchitis or emphysema.